Вплив температури на магнiторезистивнi властивостi структурно несуцiльних плiвок Fe та Co - Chornous, A. M.; Shkurdoda, Yu. O.; Loboda, V. B.; Kolomiets, V. M. (Publishing house "Academperiodika", 2018)
Magnetoresistive properties of ultrathin Fe and Co films with effective thicknesses d =3÷30 nm are studied in a temperature interval of (150–700) K. For films with d =3÷10 nm, the electrical conductivity is found to be thermally activated and the tunnel magnetoresistance effect is revealed. A decrease of the temperature down to 150 K in measurements on as-condensed films is found to result in the appearance of the magnetoresistive hysteresis and a reduction of the tunnel magnetoresistance (TMR) in a thickness interval of 10–15 nm. The maximum TMR value in the fields up to 0.7 T amounted to 1% for the as-condensed Fe films with an effective thickness of 17 nm and the Fe films with an effective thickness of 8 nm annealed at a temperature of 520 K.